Motif dan Teknik Batik Khas Kerinci: Studi di Rumah Batik Ardinal Desa Lubuk Nagodang - Billa, Weghia Oksa; Jupriani, Jupriani (TSAQOFAH, 2025)
This study aims to examine the variety of motifs and techniques used in the creation of batik specific to Kerinci, as developed at Rumah Batik Kerinci Ardinal in Lubuk Nagodang Village, Kerinci Regency. The research is grounded in the urgency to preserve local cultural heritage, which is increasingly at risk due to limited documentation and low youth engagement. Employing a descriptive qualitative approach, data were collected through observation, in-depth interviews with the studio owner, and visual documentation. The findings reveal that Rumah Batik Kerinci Ardinal plays a strategic role as both a production center and a creative educational space dedicated to preserving the traditional batik art of Kerinci. The motifs produced feature strong local identity and symbolic meaning, including Tari Ayun Luci, Lukah, Gunung Kerinci, and Aksara Incung, reflecting the region's natural richness and cultural values. The batik is crafted using synthetic stamp techniques, with production stages that demonstrate the distinctive skills of local artisans. The study concludes that documentation, revitalization, and generational renewal are essential strategies for safeguarding regional cultural heritage. The implications support the development of batik as a sustainable textile craft that not only reinforces Kerinci’s cultural identity but also opens economic opportunities within the creative sector.